Transisi New Normal: Bagaimana Masyarakat Rural dapat Bertahan? - Pratiwi Nurhabibi; Rahmadhona Fitri Helmi; Iip Permana; Fajar Ruddin; Boni Saputra (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2022)
The Indonesian government has declared a new order to live side by side with COVID-19, through the idea of a "new normal". An interesting study to see how the Indonesian people respond to this new normal policy, especially in rural communities. So far, most discussions about the new normal have only been in the context of urban society. This study aims to identify the resilience of rural communities in facing the new normal situation. The method used is qualitative with a phenomenological approach. Data was collected using in-depth interview techniques with key actors. The research was conducted in Pulo Pitu Marihat Village, Ujung Padang District, Simalungun Regency, North Sumatra Province. This area was a red zone location when the pandemic took place, and most of the population worked in the informal sector which tended to be economically and socially vulnerable. The results show that people's ability to survive in the face of changes in the new normal transition period is influenced by individual resilience, social capital, natural resource environment, and social institutions.